Organisational Prototyping: Adopting CSCW Applications in Organisations - Bardram, Jakob (DAIMI Report Series, 1997)
The usefulness of applications which support cooperative work depends in its very nature on the way the cooperative work practice is organised. At the same time, the adoption of new technology is difficult and complex because of the amount of people involved and their distribution in time and space. This paper explores the possibilities of addressing this adoption process in a more simplified, yet systematic way without losing the focus on the interdependencies which characterise cooperative work. The notion of adoption is discussed as a dual process of adapting both the computer support to the work and adapting the work to the computer. A method called organisational prototyping is presented which aims at facilitating this adoption process. A case illustrates how organisa- tional prototyping was used in the adoption of a cooperative tool for managing projects within a large engineering company in Denmark.